A practical approach to pediatric anesthesia 2026-02-16T12:07:58+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Holzman, Robert S., 1951-; Mancuso, Thomas J.; Polaner, David M. (Practical approach to anesthesia, 2016)

(untitled)
This new addition to the highly successful Practical Approach to Anesthesia series is a comprehensive, accessible guide to pediatric anesthesia, with the substance and depth of a textbook and the convenient, user-friendly features of a handbook. This guide focuses on clinical issues, contains enough academic material for board review, and is written in bulleted and outline format, with numerous illustrations and tables. Major sections focus on approach to the pediatric patient, clinical and operational aspects of pediatric anesthesia, anesthetic management of normalities and abnormalities of each organ system, and special situations such as fetal surgery, anesthesia outside the operating room, and trauma. Emphasis is on the developmental aspects--anatomic, physiologic, and pharmacologic--that require special attention in anesthesia planning--Publisher's description